PID Controlling Approach Based on FBG Array Measurements for Laser Ablation of Pancreatic Tissues - Korganbayev, Sanzhar; Orrico, Annalisa; Bianchi, Leonardo; Paloschi, Davide; Wolf, Alexey; Dostovalov, Alexander; Saccomandi, Paola (IEEE transactions on instrumentation and measurement, 2021)
In this article, we propose a temperature-based proportional-integral-derivative (PID) controlling algorithm using highly dense fiber Bragg grating (FBG) arrays for laser ablation (LA) of ex vivo pancreatic tissues. Custom-made highly dense FBG arrays with a spatial resolution of 1.2 mm were fabricated with the femtosecond point-by-point writing technology and optimized for LA applications. In order to obtain proper PID gain values, finite element method-based iterative simulation of different PID gains was performed. Then, the proposed algorithm, with numerically derived PID gains, was experimentally validated. In the experiments, the point temperature was controlled at different distances from the laser fiber tip (6.0, 7.2, 8.4, and 10.8 mm). The obtained results report robust controlling and correlation between controlled distance and the resulting area of ablation. The results of the work encourage further investigation of FBG array application for LA control.